1998
DOI: 10.1051/lait:1998440
|View full text |Cite
|
Sign up to set email alerts
|

Excretion, through milk, of ptaquiloside in bracken-fed cows. A quantitative assessment

Abstract: -The content of ptaquiloside (ptaq), a major Pteridium aquilinum carcinogen found in milk from cows fed bracken in Venezuela, has been estimated quantitatively in ils passage through bovines into milk. Six cows were given 6 kg/animal/d of fresh bracken fronds whose ptaq content was determined. Ptaq first appeared in milk 38 h after initially feeding this plant to the cows and continued to be excreted at a relatively constant level, after an induction period, for 62-70 h after the bracken diet had ceased. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
0
30
0
3
Order By: Relevance
“…They also report that ptaquiloside is carcinogenic and that very low concentrations can be dangerous to humans in drinking water. When cows eat ptaquiloside, the toxin can accumulate in milk (Alonso-Amelot et al 1998).…”
Section: Direct Effects Of Invasive Plants-litter and Exudatesmentioning
confidence: 99%
“…They also report that ptaquiloside is carcinogenic and that very low concentrations can be dangerous to humans in drinking water. When cows eat ptaquiloside, the toxin can accumulate in milk (Alonso-Amelot et al 1998).…”
Section: Direct Effects Of Invasive Plants-litter and Exudatesmentioning
confidence: 99%
“…Bovinos que consomem Pteridium spp. apresentam resíduos de ptaquilo-sídeo, uma substância cancerígena presente nessa planta (Hirono et al 1984), no leite e na carne, em quantidades variáveis (Alonso-Amelot et al 1996, 1998, Fletcher et al 2011, Calderón et al 2013. Embora o efeito carcinogênico da ingestão deste cancerígeno por humanos, juntamente com o leite ou carne contaminados, não seja confirmado, alguns autores acreditam que exista uma relação entre a incidência de neoplasias gástricas em humanos e a ingestão de ptaquilosídeo em regiões invadidas por Pteridium spp.…”
Section: Discussionunclassified
“…While these results clearly established a bridge for the passage of these carcinogens from bracken to people's diet, the question remained as to how much of this compound could be present in milk from these animals and if this quantity represented a real human health risk. A recent quantitative estimate [108] showed that 8% of the total ptaquiloside consumed in a 5 day period ended up in the excreted milk in the same period of time. Moreover, the correlation between ingested and excreted illudane was linear in the 2.4 g to 10.0 g per animal/day range.…”
Section: But Where Is the Connection?mentioning
confidence: 99%